Experimental studies and numerical modelling of heat and mass transfer process in shell-and-tube heat exchangers with compact arrangements of tube bundles - Gorobets Valery; Bohdan Yurii; Trokhaniak Viktor; Antypov Ievgen (MATEC Web of Conferences, 2018)
Shall-and-tube heat exchangers based on the bundles with in-line or staggered arrangements have been widely used in industry and power engineering. A large number of theoretical and experimental works are devoted to study of hydrodynamic and heat transfer processes in such bundles. In that, works the basic studies of heat and mass transfer for these bundles are found. However, heat exchangers of this type can have big dimensions and mass. One of the ways to improve the weight and dimensions of the shell-and-tube heat exchangers is to use compact arrangement of tube bundles. A new design of heat exchanger is proposed, in which there are no gaps between adjacent tubes that touch each other. Different geometry of these tube bundles with displacement of adjacent tubes in the direction of transverse to the flow is considered. Numerical modelling and experimental investigations of hydrodynamic, heat and mass transfer processes in such tube bundles has been carried out. The distribution of velocities, temperatures, and pressure in inter-tube channels have been obtained.